Autocuidado como método de fotoprotección en adultos jóvenes - Joselyn Nathaly, Azogue Toapanta (2023)
ABSTRACT: Self-care in photoprotection and its consequences for the skin are topics that few people are aware of it. The lack of use of this strategy affects the entire population's health, especially young adults due to overexposure to the sun due to multiple outdoor activities. Therefore, the present literature review study aims to systematize information on photoprotection, skin self-care, and possible complications in young adults affected by overexposure to the sun's rays. The methodology used was descriptive by searching for information in databases and using descriptors. Several studies indicate the minimal frequency of applying photoprotective strategies and that only specific effective photoprotective measures are used, including using hats, caps, clothing, sunglasses, and sunscreen creams. The authors conclude that carcinoma, non-carcinoma, skin cancer, and burns are the most frequent complications. Thus, there is evidence of a lack of self-care in this population group, establishing the need to implement health promotion and disease prevention measures by health personnel to make photoprotection a habit, considering the postulates set out in Dorothea Orem's nursing theory.